Giant resistance switching effect in nano-scale twinned La₀.₆₅Ca₀.₃₅MnO₃ film - Prokhorov, V.G.; Kaminsky, G.G.; Komashko, V.A.; Lee, Y.P.; Tovstolytkin, A.I.; Pogorily, A.N. (Физика низких температур, 2002)
The magnetic and transport properties of a 20 nm-scale twinned La₀.₆₅Ca₀.₃₅ MnO₃ film are investigated in a temperature range of 77-300 K. The coexistence of ferromagnetic metallic and charge-ordered insulating phases is suggested by analyzing the temperature and current dependences of the resistance at low temperatures. It is shown that thermocycling leads to the formation of a nonequilibrium state in the ensemble of charge-ordered domains and to the appearance of a giant switching in resistance of up to 100%. The experimental results are discussed on the basis of phase separation.